Análisis crítico a los agro(bio)combustibles - Martínez Castillo, Róger (2009)
Industry, governments, and scientists that promote biofuels think these will become an alternative to oil, which is running out. These new fuels are supposed to help in containing climate change through greenhouse gas emission reduction, increasing farmers´ incomes, and promoting rural development. However, rigorous research and analyses undertaken by serious ecologists and social scientists suggests that the current boom in biofuels industry will be disastrous for farmers, the natural environment, the preservation of biodiversity, and particularly for poor consumers.